Silver nanoparticles encapsulated in silica: Synthesis, characterization and application as antibacterial fillers in the ethylene polymerization. (August 2019) - Pavoski, Giovani; Baldisserotto, Daniel Luiz Stamm; Maraschin, Thuany; Brum, Luiz Fernando Wentz; dos Santos, Cristiane; dos Santos, João Henrique Zimnoch; Brandelli, Adriano; Galland, Griselda Barrera
Graphical abstract: Highlights: Silver nanoparticles obtained with three different reducing agents of silver nitrate were compared. Silver nanoparticles encapsulated in silica were used as fillers in the polymerization of ethylene. Antibacterial thermoplastics with the properties of polyethylene were developed. These materials have the potential to be used in antibacterial packages and to sterilize instruments. Abstract: Silver nanoparticles (AgNPs) were synthesized via three routes where silver was reduced by either citric acid (R1), glucose (R2) or glycerol (R3), and were stabilized with (3-aminopropyl) triethoxysilane (APTES). All nanoparticles were encapsulated in silica by the sol-gel process (SiAgE). Structural, textural, morphological and antibacterial properties of SiAgE were determined by: SEM, TGA, XRD, UV–VIS, FT-IR, BET, SAXS and disc diffusion. These SiAgE had antimicrobial properties, and they were used in ethylene polymerization using the Cp2 ZrCl2 /MAO catalytic system. The catalytic activities were high, and the percentages by weight of the fillers ranged from 1.1 to 1.6 wt%. The antibacterial properties of the nanocomposite films were studied by two tests: disc diffusion and the Parallel Streak method. The polyethylene (PE)/SiAgE nanocomposites inhibited the proliferation of Staphylococcus aureus (Gram positive) and Escherichia coli (Gram negative) bacteria in contact with the films, thus showing potential to be used as active packages in medicine.